2009
DOI: 10.1016/j.amepre.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-Free Policies Among Asian-American Women

Abstract: Background California has significantly decreased racial/ethnic and educational disparities in smoke-free home and indoor work policies. California's ethnic-specific surveys present an opportunity to disaggregate data and examine the impact of California's smoke-free social norm campaign for Asian-American women. Methods The California Tobacco Use Surveys for Chinese Americans and Korean Americans were conducted in 2003 and analyzed in 2008 to compare women with lower (≤ high school graduate) or higher educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…Although declining response rates have already been observed in statewide tobacco surveys for the general population in California and Massachusetts, there is no evidence that this has resulted in different representation of population subgroups and any less accurate or biased estimates of smoking behavior (Biener, Garrett, Gilpin, Roman, & Currivan, 2004). In comparison with the California tobacco surveys for other Asian American subgroups that used similar methodology, our study achieved a higher participation rate of eligible contacted participants (63.5%) than the surveys for Chinese Americans (52%) or Korean Americans (48%; Tong, Tang, et al, 2009). …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although declining response rates have already been observed in statewide tobacco surveys for the general population in California and Massachusetts, there is no evidence that this has resulted in different representation of population subgroups and any less accurate or biased estimates of smoking behavior (Biener, Garrett, Gilpin, Roman, & Currivan, 2004). In comparison with the California tobacco surveys for other Asian American subgroups that used similar methodology, our study achieved a higher participation rate of eligible contacted participants (63.5%) than the surveys for Chinese Americans (52%) or Korean Americans (48%; Tong, Tang, et al, 2009). …”
Section: Discussionmentioning
confidence: 84%
“…We modified the age variable into a continuous variable with 10-year increments and the education variable into lower (less than or equal to high school) versus higher (more than or equal to some college) educational levels in order to facilitate our interaction analysis. The education variable was dichotomized since the lower education levels were behaving in a similar manner as were the higher education levels, and this categorization has been used in other Asian American surveys (Tong, Tang, Tsoh, Wong, & Chen, 2009). We calculated adjusted odds ratio with 95% CIs, with a significance level of p < .05 for all statistical tests.…”
Section: Data Analysesmentioning
confidence: 99%
“…In California, a US state which has comprehensive smoke-free legislation, low SES women reported higher workplace exposure to SHS, more exposure to SHS in the home and less control over home smoking policies than high SES women 87. Comprehensive smoke-free public places legislation can also encourage home smoking restrictions and reductions in children's exposure to SHS.…”
Section: The Impact Of Tobacco Control Policies On Women and Girlsmentioning
confidence: 99%
“…Those who had low income and people who live in Central and Southern Taiwan were more likely to report household SHS exposure. A study found disadvantaged women were more likely exposed to SHS at home because of their lack of power and ability to negotiate smoke-free home policies (Tong, Tang, Tsoh, Wong, & Chen, 2009). Media campaigns, community education programs about the harm of SHS, smoking cessation services, smoke-free home policies, and other tobacco control measures should continue to be promoted to maximize their effect on reducing smoking prevalence and household SHS exposure.…”
Section: Discussionmentioning
confidence: 98%